1989
DOI: 10.1093/nar/17.8.3247
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahymenamicronuclear sequences that function as telomeres in yeast

Abstract: We explored the ability of S. cerevisiae to utilize heterologous DNA sequences as telomeres by cloning germline (micronuclear) DNA from Tetrahymena thermophila on a linear yeast plasmid that selects for telomere function. The only Tetrahymena sequences that functioned in this assay were (C4A2)n repeats. Moreover, these repeats did not have to be derived from Tetrahymena telomeres, although we show hat micronuclear telomeres (ike macronuclear telomeres) of Tetrahymena trminate in (C4A2)n repeats. Chromosome-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…On the basis of our data and that of others (Murray et al 1988;Shampay and Blackburn 1989), we propose that telomerase in yeast is incapable, itself, of establishing a new telomere. It requires the presence of an organizer sequence such as (T2G4) n nearby.…”
Section: A Role For An Organizer Sequence Such As (T2g4) Nsupporting
confidence: 70%
See 1 more Smart Citation
“…On the basis of our data and that of others (Murray et al 1988;Shampay and Blackburn 1989), we propose that telomerase in yeast is incapable, itself, of establishing a new telomere. It requires the presence of an organizer sequence such as (T2G4) n nearby.…”
Section: A Role For An Organizer Sequence Such As (T2g4) Nsupporting
confidence: 70%
“…It is well documented that Tetrahymena T~G4 is a good substrate for the de novo addition of yeast TGI_3 sequences (Szostak and Blackburn 1982;Shampay et al 1984;Murray et al 1988;Shampay and Blackburn 1989). We therefore chose to look at the cases where nontelomeric DNA was used as the addition site.…”
Section: Addition Sites For Yeast Tgi_3 Are Short Stretches Of G T Omentioning
confidence: 99%
“…Previous results from T. thermophila (Shampay and Blackburn 1989) and the hypotrichous ciliate Oxytricha fallax (Dawson and Herrick 1984)have indicated the probability that ciliate micronuclear telomeres contain the same repeat sequence as their macronuclear counterparts. We report that the distal telomeric repeat sequence in the T. thermophila micronucleus is the same as that found in the macronucleus, but the micronuclear telomere sequence is nonetheless unique in several respects.…”
Section: Discussionmentioning
confidence: 99%
“…Initial hybridization studies indicated that micronuclear telomeres contain the same repeat sequence (Shampay and Blackburn 1989). However, these telomeres have been very difficult to identify largely because of two reasons.…”
Section: Identification Of Micronuclear Telomeresmentioning
confidence: 99%
See 1 more Smart Citation